Prevalence of Social Determinants of Health Among Health System Employees - Eileen L. Seeholzer; Marielee Santiago; Charles Thomas; Monica DeAngelis; Francesca Scarl; Anastasia Webb; Tangela Woods; Ashwini R. Sehgal (SAGE Publishing, 2022)
Introduction/Objectives: Many health systems screen patients for social determinants of health and refer patients with social needs to community service organizations for assistance. However, little is known about social determinants of health among health system employees. We sought to examine the prevalence of social determinants among employees of The MetroHealth System, a large safety-net health system in Cleveland, Ohio. Methods: We invited participants in an employee wellness program to answer the same screening questions that patients answer about 9 social determinants of health, including food insecurity, financial strain, transportation difficulty, inability to pay for housing or utilities, intimate partner violence, social isolation, infrequent physical activity, daily stress, and lack of internet access. We then determined the percentage of employees who met pre-defined criteria for being at risk for each social determinant. We also examined how these percentages varied across employee job categories. Results: Of 4191 full-time employees, 1932 (46%) completed the survey. The percentage of employees at risk for each social determinant were: food insecurity (11%), financial strain (12%), transportation difficulty (4%), inability to pay for housing or utilities (10%), intimate partner violence (4%), social isolation (48%), infrequent physical activity (10%), daily stress (58%), and lack of internet access (3%). Being at risk for specific social determinants was more common among support staff compared to staff physicians and nurses. For example, the survey participants included 436 administrative support staff, a job category that includes secretaries and patient service representatives. Among this group, 20% reported food insecurity, 20% financial strain, and 17% inability to pay for housing or utilities. Conclusions: Social determinants of health are common among health system employees, especially among workers in lower paid job categories. Health systems should routinely screen employees for social determinants and adjust salaries, benefits, and assistance programs to address their social needs.